BIM Standards Around The World – A Review of BIM Standards in the Global AEC Industry and BIM Roles of Project Stakeholders - Abuebeid, Marwan; Nielsen, Y (2018)
This paper investigates the nature of national BIM standards amoung various countries and examine the presence of standards that clarify the BIM roles of project stakeholders such as project management consultant (PMC) at the various stages of the construction project lifecycle, including inception, design and construction. A research has been conducted which case BIM studies from UK, Norway, Finland, US, Canada, Singapore and Australia were reviewed. The study indicates that current BIM standards have mainly focused on explaining the model standards and BIM requirements. There are only a few national standards, such as the case of Singapore, which highlight the BIM objectives at each stage of the construction process, the project stakeholders that should be involved, and the deliverables. The specific roles of the various project stakeholders for each objective are not adequately clarified and hence likely to vary from one project and organization to another.